Tax Service Satisfaction Analysis Using the Servqual Method - Importance and Performance Analysis at the Regional Revenue Agency of Jeneponto Regency - Muhammad Nusran; Muh. Irsal Hidayat; Anis Saleh (Indonesian Journal of Economic & Management Sciences, 2024)
Service quality plays a crucial role in shaping the public's positive perception. This study applies the "Importance and Performance Analysis (IPA)" method to assess five dimensions of service quality at the Regional Revenue Agency of Jeneponto Regency, namely physical evidence, reliability, responsiveness, assurance, and empathy. Data were collected through interviews, observations, and questionnaires. The results show that the average service quality score of 0.9910 is still below customer expectations and requires improvement, especially in the reliability dimension with the largest gap (-0.4688). The attributes most influencing customer satisfaction include quick response, clarity of regulations, information security, physical facilities, reliable assistance, and employees' concern for individual taxpayer situations